K- and L-shell theoretical fluorescence yields for the Fe isonuclear sequence. (February 2023) - Pinheiro, Daniel; Fernandes, André; Godinho, César; Machado, Jorge; Baptista, Gonçalo; Grilo, Filipe; Sustelo, Luís; Sampaio, Jorge M.; Amaro, Pedro; Leitão, Roberta G.; Marques, José P.; Parente, Fernando; et al.
Abstract: In this work, we present K- and L- shell fluorescence yield values of the full isonuclear sequence of Fe ions, using a state-of-the-art multiconfiguration Dirac–Fock approach. These results may be of importance for spectral fitting and plasma modeling, both in laboratory and astrophysical studies, where Fe is an important benchmark element. The K-shell fluorescence yields were found to be very similar up to the removal of 14 electrons. Highlights: We have performed K- and L- fluorescence yields of the isonuclear sequence of Fe from first principles using a multiconfiguration Dirac–Fock approach. Changes of the fluorescence yield were assessed for K- and L- shells as a function of the charge state. L1 subshell fluorescence yield is much more sensitive to the removal of outer electrons than the L2, 3 subshell fluorescence yield.